A new species of Lycodapus from the Emperor seamount chain, northwestern Pacific Ocean (Teleostei: Zoarcidae) - Prokofiev, Artem M.; Balanov, Andrei A.; Emelianova, Olga R.; Orlov, Alexei M. 1960-; Orlova, Svetlana Yu (Diversity)
A new species, Lycodapus imperatorius, is described from the seamounts of the Emperor Ridge, North Pacific Ocean. The new species can be identified by its stout gill rakers, single interorbital pore, four preopercular and four mandibular pores, 95-99 vertebrae, numerous vomerine and palatine teeth, and COI mtDNA sequences. Although the new species is most similar to L. endemoscotus and L. antarcticus in morphology, the closest match to already published sequences was Lycodapus fierasfer, which is fairly different from the new species in terms of morphology. The incongruence between molecular and morphological inferences might be explained by the homoplastic nature of the morphological characteristics used for species delimitation in Lycodapus. The percent of genetic identity between the closest species of Lycodapus ranges from 95.4 to 98.6% in comparison with 99.5-100.0% between individuals of the same valid species. A key of the genus is amended to include the new species.